SOCIAL SKILLS DEVELOPMENT FOR STUDENTS WITH AUTISM IN INCLUSIVE SCHOOLS: THAILAND - Assoc.Prof.Unchalee Sanrattana, Ph.D.; Thidakorn Maneerat; Kamonrat Srevisate (Proceedings of International Conference on Special Education, 2015)
The purpose of this research was threefold: (a) to inventory the incidence of autism among students in the educational system of Khon Kaen Province,Thailand, at each of three grade levels (kindergarten, primary and secondary), (b) to identify the most frequently occurring social skills deficits among autistic children at each of the grade levels, and (c) to develop social skills stories and assess the effectiveness of presenting those stories to a selected student at each grade level. Research found that most autistic students in regular schools were boys (78.62%). In total, 36.55 % of autistic students were studying at the kindergarten level, 55.86% were studying at the primary level, and 7.59% were studying at the secondary level. The most frequently observed deficits in social skills were in the areas of self-control behavior, communication skills and working in a team. Presentation of the social stories resulted in pronounced improvement in most areas of deficiency.